Examining Communication Patterns in a Construction Setting: An Interview-Based Study - Sta. Maria, Carlo L.; Santos, Lee Andrei L.; Cabrera, Andreu S.; Noble, C-Jay R.; Pineda, Jr., Florentino G. (Future Science / FSH-PH Publications, 2024)
The fundamental concept of this study is to explore the communication dynamics of a general contractor institution. The study examines the organizational culture and communication flow to determine the communication model employed by the institution and document its communication practices. This study employed a qualitative research approach to analyze the institution's communication dynamics in-depth. The researchers conducted an interview and documented and transcribed the responses. Thematic analysis was used to analyze the data collected from participants. The findings of this study revealed that the general contractor institution operates under a hierarchical structure but strongly emphasizes respect during interactions. Their well-organized decision-making system allows workers to raise concerns effectively. The institution adeptly uses various communication channels such as Messenger, Viber, Text Message, and Email, adapting tones to specific contexts. Challenges include industry-specific jargon, language barriers, and the influence of hierarchy on feedback dynamics. The result showed that the communication models utilized by the institution are Schramm's model and the Shannon-Weaver model, which emphasize the importance of shared meanings, standard codes, and active participation in communication. Schramm's model highlights feedback and the need for a common understanding, while the Shannon-Weaver model addresses noise reduction and the cyclical nature of communication through feedback. Overall, this study provides important insights into the communication dynamics of the general contractor institution and offers an overview of specific instances or events that have transpired within the organization.